Net ultrafiltration intensity and mortality in critically ill patients with fluid overload - Murugan, Raghavan; Balakumar, Vikram; Kerti, Samantha J.; Priyanka, Priyanka; Chang, Chung-Chou H.; Clermont, Gilles; Bellomo, Rinaldo; Palevsky, Paul M.; Kellum, John A. (Critical care (London, England), 2018)
Background Although net ultrafiltration (UF NET ) is frequently used for treatment of fluid overload in critically ill patients with acute kidney injury, the optimal intensity of UF NET is unclear. Among critically ill patients with fluid overload receiving renal replacement therapy (RRT), we examined the association between UF NET intensity and risk-adjusted 1-year mortality. Methods We selected patients with fluid overload ≥ 5% of body weight prior to initiation of RRT from a large academic medical center ICU dataset. UF NET intensity was calculated as the net volume of fluid ultrafiltered per day from initiation of either continuous or intermittent RRT until the end of ICU stay adjusted for patient hospital admission body weight. We stratified UF NET as low (≤ 20 ml/kg/day), moderate (> 20 to ≤ 25 ml/kg/day) or high (> 25 ml/kg/day) intensity. We adjusted for age, sex, body mass index, race, surgery, baseline estimated glomerular filtration rate, oliguria, first RRT modality, pre-RRT fluid balance, duration of RRT, time to RRT initiation from ICU admission, APACHE III score, mechanical ventilation use, suspected sepsis, mean arterial pressure on day 1 of RRT, cumulative fluid balance during RRT and cumulative vasopressor dose during RRT. We fitted logistic regression for 1-year mortality, Gray’s survival model and propensity matching to account for indication bias. Results Of 1075 patients, the distribution of high, moderate and low-intensity UF NET groups was 40.4%, 15.2% and 44.2% and 1-year mortality was 59.4% vs 60.2% vs 69.7%, respectively ( p = 0.003). Using logistic regression, high-intensity compared with low-intensity UF NET was associated with lower mortality (adjusted odds ratio 0.61, 95% CI 0.41–0.93, p = 0.02). Using Gray’s model, high UF NET was associated with decreased mortality up to 39 days after ICU admission (adjusted hazard ratio range 0.50–0.73). After combining low and moderate-intensity UF NET groups ( n = 258) and propensity matching with the high-intensity group ( n = 258), UF NET intensity > 25 ml/kg/day compared with ≤ 25 ml/kg/day was associated with lower mortality (57% vs 67.8%, p = 0.01). Findings were robust to several sensitivity analyses. Conclusions Among critically ill patients with ≥ 5% fluid overload and receiving RRT, UF NET intensity > 25 ml/kg/day compared with ≤ 20 ml/kg/day was associated with lower 1-year risk-adjusted mortality. Whether tolerating intensive UF NET is just a marker for recovery or a mediator requires further research.